Articles of faith religion, secularism, and the Indian Supreme Court - Sen, Ronojoy (Oxford : Oxford University Press, 2010)
As a contribution towards understanding the place of religion in modern India and the nature of Indian secularism, this book looks at the Indian Supreme Court judgments, discussing judicial interventions in areas which are important to the life of the Indian nation and Indian secularism. It argues that religious pluralism and religious tolerance are critical for the survival of the Indian nation.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: India. -- Supreme Court; Religion and state -- India -- Cases; Hinduism and state -- India -- Cases; Religious minorities -- Legal status, laws, etc. -- India -- Cases